Ventrogluteal region, an alternative location to apply benzathine penicillin - Laura Ferreira Oliveira; Priscilla Santos Junqueira; Maisa Rodrigues da Silva; Márcia Maria de Souza; Sheila Araujo Teles; Ana Luiza Neto Junqueira (Universidade Federal de Goias, 2015)
The objective of this study was to compare the pain level related to the administration of benzathine penicillin on the ventrogluteal (VG) and dorsogluteal (DG) region. A randomized controlled trial. Sixty-one people participated in the study, 31 on the intervention group (VG region), and 30 on the control (DG region). The Chi-Squared and Mann-Whitney tests were used to test differences of proportions and to compare central tendencies between groups, respectively. Values of p <0.05 were considered statistically significant. At the three assessed moments, the mean score of pain was higher when the application of the drug was on the VG region vs. DG. At the first and third minute, the difference was statistically significant. These results confirm the VG region as alternative place with less local reaction to apply intra-muscular injections.